Handbook on Immunosenescence 2009
DOI: 10.1007/978-1-4020-9063-9_64
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis, Inflammation and Ageing

Abstract: Osteoporosis is a condition characterized by low bone mass and increased bone fragility, putting patients at risk of fractures, which are major causes of morbidity substantially in older people. Osteoporosis is currently attributed to various endocrine, metabolic and mechanical factors. However, emerging clinical and molecular evidence suggests that inflammation also exerts significant influence on bone turnover, inducing osteoporosis. Numerous proinflammatory cytokines have been implicated in the regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 131 publications
(30 reference statements)
2
117
1
1
Order By: Relevance
“…Indeed, elevated plasma concentrations of IL-6, IL-1␤, and TNF-␣ have been described in elderly populations and were postulated as predictive markers of functional disability, frailty and mortality (Bruunsgaard et al, 2003;Ershler and Keller, 2000;O'Mahony et al, 1998) and it has been suggested that chronic inflammation supports the development and progression of age-related diseases, such as osteoporosis, neurodegeneration and atherosclerosis (Gao and Hong, 2008;Ginaldi et al, 2005;Libby, 2002). Subclinical inflammation may be caused by chronic stimulation of the innate immune system by degradation products and/or by the partial inability of the aged immune system to eliminate certain pathogens (Weinberger et al, 2009), this inflammatory status may slowly damage one or several organs, especially when unfavorable genetic polymorphisms and epigenetic alterations are concomitant, leading to an increased risk of frailty together with the onset of age-related chronic diseases (reviewed by Cevenini et al, 2010 andVasto et al, 2007).…”
Section: Inflamm-ageing and T Lymphocytesmentioning
confidence: 99%
“…Indeed, elevated plasma concentrations of IL-6, IL-1␤, and TNF-␣ have been described in elderly populations and were postulated as predictive markers of functional disability, frailty and mortality (Bruunsgaard et al, 2003;Ershler and Keller, 2000;O'Mahony et al, 1998) and it has been suggested that chronic inflammation supports the development and progression of age-related diseases, such as osteoporosis, neurodegeneration and atherosclerosis (Gao and Hong, 2008;Ginaldi et al, 2005;Libby, 2002). Subclinical inflammation may be caused by chronic stimulation of the innate immune system by degradation products and/or by the partial inability of the aged immune system to eliminate certain pathogens (Weinberger et al, 2009), this inflammatory status may slowly damage one or several organs, especially when unfavorable genetic polymorphisms and epigenetic alterations are concomitant, leading to an increased risk of frailty together with the onset of age-related chronic diseases (reviewed by Cevenini et al, 2010 andVasto et al, 2007).…”
Section: Inflamm-ageing and T Lymphocytesmentioning
confidence: 99%
“…Senescent cells also secrete many cytokines which, due to their diverse function, could have multiple consequences on the ageing of tissues and the development/progression of disease (Ginaldi et al 2005;Payne 2006;Salvioli et al 2006;Sue and Griffin 2006;Libby 2006). These secreted proteins may not just impact on local tissue but also tissues found throughout the organism.…”
Section: Biological Impact Of the Senescent Phenotypementioning
confidence: 99%
“…Nuclear factor kappa B (NF-κ B) receptor activator (RANK), receptor activator of NF-κ B ligand (RANKL), and osteoprotegerin (OPG) play a role in the pathogenesis of osteoporosis (Ginaldi et al 2005;Kearnes et al 2008). OPG, a soluble protein produced by osteoblasts, is a decoy receptor that can bind to RANKL, which is also produced by osteoblasts.…”
mentioning
confidence: 99%